(untitled) (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
On the basis of a survey on political views among students at universities in Hesse, the author shows that the assertion, that the left-right-dichotomy has lost empirical or theoretical evidence cannot be maintained. They belong to the symbolical order of modern politics as floating significants, although their meaning is changing at the moment.